Zabawa - Myszorek, Marzena
Keywords: fotografia; konkursy fotograficzne

Playing - Ozatay, Buket
Keywords: fotografia; konkursy fotograficzne

Playing 20 - Le, Chau Dao
Keywords: fotografia; konkursy fotograficzne; dziecko

Playing-2 - Le Chau Dao
Keywords: fotografia; konkursy fotograficzne; dziecko

Naught boys playing water - Lin Dung-Leung
Keywords: fotografia; konkursy fotograficzne; dziecko

Playing Little Monks - Debasree, Das
Keywords: fotografia; konkursy fotograficzne; dziecko

Playing in the bubble - Aranha, Guacyr
Keywords: fotografia; konkursy fotograficzne; dziecko

Motor and psychological predispositions for playing football - Kalinowski, Paweł; Bojkowski, Łukasz; Śliwowski, Robert (Akademia Wychowania Fizycznego w Poznaniu)
Nowadays football is steadily developing around the world. Many sport theorists and practitioners pay a lot of attention to the search for the key factors determining high sports results. Players’ comprehensive preparation seems to be essential in order to succeed in football. Therefore, the focus of this work was on the aspects of fitness and mental preparation. The authors aimed to define the basic motor skills and psychological conditions, designed to serve as predisposition to sports competition in an11-person football. Among the motor factors, a special attention was drawn to the importance of endurance and speed ability in football. As far as the psychological conditions are concerned, the role of the psychosocial prototype of a high-performance sporting situation and psychological characteristics determining success in football were emphasized.
Keywords: predispositions; football; motor skills; psychology

Improving attentional processes in sport; sport specific issues during effective playing time - Schefke, Tomasz; Gronek, Piotr (Akademia Wychowania Fizycznego w Poznaniu)
Keywords: attention; tennis; playing time

Playing football in the Sosnowiec area during the period of World War II (1943-1944) - Ponczek, Mirosław (Akademia Wychowania Fizycznego w Poznaniu)
Keywords: football history; war and sports

Variations of technical actions among playing positions in male high level volleyball - Lima, Ricardo Franco; Caleiro, Francisco; Clemente, Filipe Manuel (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Volleyball is a team sport in which a mistake made by a player on one team gives a point to the opponent. This fact requires coaches to think of all volleyball skills as having the same level of importance. Aim of Study. The purpose of this study was to analyze and compare variations of the technical actions of players’ in-game role in terms of total points, breaking points, and the point/error relationship during one professional season. Material and Methods. The study included 80 matches played by 14 teams participating in the male First Division Portuguese Championship during the 2017/2018 season. The study analyzed 295 sets with a total of 85,233 actions. Data was collected using the statistical programs Data Volley and Click & Scout after video recording the matches. Results. Considering breaking points, moderate decreases were found for middle blockers vs opposites, and small increases were found for outside hitters vs middle blockers. Also, small increases were found for outside hitters vs opposites. Considering the point/error relationship, small decreases were found for middle blockers vs opposites and for outside hitters vs opposites. Trivial differences were found between outside hitters and middle blockers. Conclusions. The main differences portrayed in the study show that to have success, during practice, coaches need to focus on improving players’ efficiency in different game actions in the counter-attack phase.
Keywords: match analysis; player role; elite players; notational analysis; performance